Redox activities of mono- and binuclear forms of low-molecular and protein-bound dinitrosyl iron complexes with thiol-containing ligands - Borodulin, Rostislav R.; Dereven’kov, Ilia A.; Burbaev, Dosymzhan Sh.; Makarov, Sergei V.; Mikoyan, Vasak D.; Serezhenkov, Vladimir А.; Kubrina, Lyudmila N; Ivanovic-Burmazovic, Ivana; Vanin, Anatoly F. (Nitric Oxide - Biology and Chemistry, 2014)
EPR, optical, electrochemical and stopped-flow methods were used to demonstrate that Fe(NO) fragments in paramagnetic mononuclear and diamagnetic binuclear forms of dinitrosyl iron complexes with glutathione are reversibly reduced by a two-electron mechanism to be further transformed from the initial state with d configuration into states with the d and d electronic configurations of the iron atom. Under these conditions, both forms of DNIC display identical optical and EPR characteristics in state d suggesting that reduction of the binuclear form of DNIC initiates their reversible decomposition into two mononuclear dinitrosyl iron fragments, one of which is EPR-silent (d ) and the other one is EPR-active (d). Both forms of DNIC produce EPR signals with the following values of the g-factor: g = 2.01, g = 1.97, g = 2.0. M-DNIC with glutathione manifest an ability to pass into state d, however, only in solutions with a low content of free glutathione. Similar transitions were established for protein-bound M- and B-DNIC with thiol-containing ligands. © 2014 Elsevier Ltd. All rights reserved.
Keywords: Cyclic voltammetry; Dinitrosyl iron complexes; Redox conversions